Anesthesia for Cesarean Section and Emergency Abdominal Surgeries When No Anesthetist Is Available [24R]. (May 2016) - Eckardt, Melody; Guha, Moytrayee; Altawil, Zaid; Nelson, Brett; Ahn, Roy; Burke, Thomas
Abstract : INTRODUCTION: The worldwide human resource gap in anesthesia services is one of the major barriers to accessing cesarean section and other emergency abdominal surgeries. This study assessed the impact of a novel ketamine anesthesia package, called Every Second Matters-Ketamine (ESM-Ketamine TM ), for use in cesarean sections and emergency abdominal surgeries by non-anesthetist clinicians when no anesthetist was available. METHODS: Non-anesthetist clinicians from five hospitals underwent a five-day training course on ESM-Ketamine complemented by checklists and an ESM-Ketamine Kit. A database was established which captured pre-, intra-, and postoperative details each time ESM-Ketamine was invoked. All cesarean section and emergency abdominal surgery cases extracted from the larger database were analyzed. Primary outcome measures centered on the ability to safely support these emergency surgeries. RESULTS: Twenty providers were trained on ESM-Ketamine and overall supported 346 operations when no anesthetist was available. Of the 346 surgeries, 70 were emergency cesarean sections and 21 emergency laparotomies. Brief (less than 30 seconds) patient desaturation below 92% and hallucinations occurred in 5 (5.5%) and 7 (7.7%) of the 91 patients, respectively. There were no major adverse events such as death, prolonged desaturations, or injuries as a result of ESM-Ketamine. CONCLUSION: This study provides promising preliminary evidence that the ESM-Ketamine package may significantly increase access to life-saving cesarean sections in resource-limited settings when no anesthetist is available.